Aleister Crowley and the temptation of politics - Pasi, Marco; Cambridge eBooks (Durham : Acumen Publishing, 2014)
Aleister Crowley (1875-1947) is one of the most famous and significant authors in the history of western esotericism. Crowley has been long ignored by scholars of religion whilst the stories of magical and sexual practice which circulate about him continue to attract popular interest. Aleister Crowley and the Temptation of Politics looks at the man behind the myth - by setting him firmly within the politics of his time - and the development of his ideas through his extensive and extraordinarily varied writings. Crowley was a rationalist, sympathetic to the values of the Enlightenment, but also a romantic and a reactionary. His search for an alternative way to express his religious feelings led him to elaborate his own vision of social and political change. Crowley's complex politics led to his involvement with many key individuals, organisations and groups of his day - the secret service of various countries, the German Nazi party, Russian political activists, journalists and politicians of various persuasions, as well as other writers - both in Europe and America. Aleister Crowley and the Temptation of Politics presents a life of ideas, an examination of a man shaped by and shaping the politics of his times.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Crowley, Aleister, -- 1875-1947.; Crowley, Aleister, -- 1875-1947 -- Political and social views; Electronic books